Peningkatan Pengetahuan Ibu Hamil Tentang Tanda Bahaya Kehamilan Melalui Edukasi Berbasis Leaflet Di Posyandu - Treasa, Adisty Dwi; Srifitayani, Nur Rahma; Hamzah, Ricda Nurhikmayanti; Dewi, Ratna; Ahmad, Nurul Fuady Fitryani (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2025)
Pregnancy danger signs are conditions that can threaten the safety of the mother and fetus if not recognized and treated quickly. Lack of knowledge of pregnant women regarding pregnancy danger signs is one of the causes of the high rate of pregnancy complications. This community service aims to increase the knowledge of pregnant women about pregnancy danger signs through leaflet-based education at Posyandu. The method of implementing the activity includes counseling with leaflet media and interactive discussions. The results of the activity showed an increase in the knowledge of pregnant women after education was carried out. This activity shows that leaflet media is effective in increasing the knowledge of pregnant women about pregnancy danger signs.